Semiotic Analysis Of Film Paskal According To The Islamic Principles Of Syed Muhammad Naquib Al-Attas' Thinking And Its Impact On Linguistic Content/ التحليل السيميائي لفلم باسكال في ضوء أصول الفكر الإسلامي لسيد محمد نقيب العطاس أثرها في المحتوى اللغوي - H. Osman, Rahmah Ahmad; Alosman, Abdulrahman; Che Amran, Aisyah Aminah; Idris, Isyah Radhiah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Films have a significant impact on the Muslim community in Malaysia due to their content; watching the film affects them with an understanding of Islam or otherwise based on its content, and watching the film also assists Arabic language students in learning language studies from the film, such as analyzing the linguistic knowledge found in the film. This study sought to uncover Said Muhammad Naquib Al-Attas' core notions about the nature of knowledge from an Islamic perspective by applying them to the film Paskal and showing the Islamization of the Malay language used in the film. The current study depended on the descriptive analytical technique, where the semiotic tool was employed when studying the film's content to obtain deeper Islamic notions from the perspective of Al-Attas. The most significant finding from this study's conclusion is that the Malay film contains numerous scenarios that illustrate the seven Islamic ideals from Sayd Muhammad Naquib Al-Attas's perspective: religion, humanity, science and knowledge, wisdom, justice, literature, college and university. In addition, the term Islamization of the Malay language refers to using Islamic Arabic terminology in Malay. In this film, loanwords in Arabic are used often, totaling 28 words, and two Malay terms that convey Islamic connotations.